THE ARGUMENT AND DEMONSTRATION EXEMPLIFIED IN A MATHEMATICAL DIALOGUE - Marcos Campos Nava; Luisa Morales Maure; Orlando GarcÃa MarimÃ³n; Jaime GutiÃ©rrez (IKIP Siliwangi and I-MES, 2022)
The teaching-learning process is analyzed in a course for a group of professors who were taught subjects on Calculus, to study the episodes of problem-solving in them, focused on the identification of patterns and argumentation using counterexamples. The explanation and the argument in the classroom can be used together so that the argument (issued as a counterexample) supports the explanation (conjecture). Developing the mathematics class so that the above occurs is a form of interaction and how to encourage students to move from explanation to argumentation (placing a hybrid system). Furthermore, both forms of reasoning can influence dialogue protocols and strategies. In this work, the dialogue model is described as a tool to address the problem that arises when working with students.